Implementation of Photodiode Sensors in a Line Follower Robot - Herizon, Herizon; Yuliza, Milda; Rahmat, Rahmat (JECCOM: International Journal of Electronics Engineering and Applied Science, 2024)
Line follower robot is a type of autonomous robot designed to follow a specific trajectory, usually a black line on a white background. In order for the robot to follow the trajectory accurately, a sensor is required that is able to detect the difference in light intensity between the line and the background. This study evaluates the application of a photodiode sensor to a microcontroller-based line follower robot, focusing on the performance of the sensor under various lighting conditions and surfaces. The results show that the photodiode sensor is able to detect lines with high accuracy of almost 100% between black lines on a white surface. To achieve fast response speed and high trajectory stability, the optimal distance between the photodiode sensor and the surface must be maintained. Fast response speed and high trajectory stability are at a distance of 0.5 to 1.0 cm. Under normal lighting conditions (200-300 lux), the robot can follow the trajectory with optimal speed and precision. Under low lighting conditions (below 100 lux), the sensor is still able to detect the line, but the robot speed must be reduced to maintain accuracy. Under very bright lighting conditions (above 500 lux), the photodiode sensor shows a little difficulty in distinguishing lines if there is significant light reflection, but it can still be compensated by adjusting the sensor sensitivity. This research provides a solid foundation for further development in improving the performance of line follower robots in various practical applications.